Persoalan Kemiskinan Perkotaan - Abdul Wahab; Sudirman Sudirman (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The research objective is to observe the problem of poverty in urban areas. This research method uses descriptive qualitative methods. The results of the research show that the factors that cause poverty are: 1). Low education. 2). Lazy Job. 3). Limited Natural Resources. 4). Limited Employment. 5). Capital Limitations. 6). Family Burden. The forms of efforts that must be made in overcoming poverty efforts are including counseling and social guidance, providing social services, providing access to work and business opportunities, obtaining basic health services, obtaining basic education, providing housing and settlements that are clean and feasible, provide access to training, provide business capital for underprivileged communities, and carry out marketing of business results. The conclusion of this study is that the urban poor have relatively more difficulty meeting their basic needs than those in the countryside. In rural areas, without money people can still eat with garden produce, although it is relatively small, but in cities without money, it is impossible for the poor to get anything if they don't get help from other people. Keywords: Poverty, Urban Problems, Urban Sociology